EFFECTIVENESS OF ENVIRONMENTAL LAW ENFORCEMENT IN MANOKWARI REGENCY - Frengky Ever Wambrauw; A. M. Yunus Wahid; Maskun (International Peneliti Ekonomi, Sosial dan Teknologi, 2023)
The purpose of this study was to analyze the effectiveness of environmental law enforcement against law violations committed by PT. Medcopapua Hijau Selaras (PT. MPHS) in Manokwari Regency. The type of research that the author uses is empirical legal research, with a case approach that examines legal provisions related to the environment that regulate and establish an environmental law enforcement system for cases of environmental impacts resulting from the activities of the palm oil company PT. Medcopapua Hijau Selaras in Sidey District, Manokwari Regency, West Papua Province. The data used are primary data and secondary data obtained through interviews and literature. The data obtained both primary and secondary data were categorized according to the type of data, then the data were analyzed qualitatively. The results of this study indicate that environmental law enforcement against PT. MPHS is not effective, this can be shown through the behavior of law enforcers who are not reasonable in handling a case. PT. MPHS pollutes the environment through its operational waste, causing a decrease in the quality of water consumed by the community on a daily basis. Moreover, there are no civil lawsuits from the government, the public, and environmental organizations and there are no definite legal steps against the alleged waste pollution case from PT. MPHS. Even though PT. MPHS has been subject to administrative sanctions three times and deserves to be prosecuted or revoked.